(untitled) (Fiep Bulletin - online, 2016)
This article derives from a lecture prepared for the Master’s Program in Translational Biomedicine - Biotrans / UNIGRANRIO, campus Duque de Caxias, in April 2015. The proposal was interdisciplinary: bring a perspective of the humanities, culture and arts to an audience of biomedicine’s students with the theme obesity that was more familiar to students by health’s bias. The objective was to show that obesity has always draws attention. In any problem or solution, as a threat to health or synonymous with progress and beauty, the obesity pictures, independent of the writing style, formulate their own discourse acting in culture, imposing standards to be followed or rejected. By philosophical bias, it is addressing the great moments of fixing food idea with the concepts that serve as the backdrop to think about the link between diet and right aesthetic parameter. The Italian cinema, the image of stylized woman by Federico Fellini produces a critical kind of caricature of women in film. Finally, traversing some of the Last Supper pictures painted at different times, it highlights the metaphor of transubstantiation with the food.